2018
DOI: 10.1159/000487002
|View full text |Cite
|
Sign up to set email alerts
|

Giant Congenital Melanocytic Nevi: An Update and Emerging Therapies

Abstract: Giant congenital melanocytic nevi (GCMN) are a rare occurrence. Gain-of-function mutation in the NRAS gene is found to be associated with GCMN, causing abnormal proliferation of embryonic melanoblasts. The two major complications associated with GCMN are malignant melanoma and neurocutaneous melanosis. Treatment of GCMN has conventionally been surgical. However, the role of NRAS inhibitors and inactivation of nevus tissue by high hydrostatic pressure are being explored. We present a case of a 1-day-old neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…4 The activation of these signaling pathways leads to melanocyte growth, proliferation, survival, and transformation. 1 Although inhibition of the MAPK pathway has been targeted in the treatment of numerous malignancies (including melanoma), no reports of its successful use in the treatment of benign cellular proliferations, such as complex GCMNs and neurocutaneous melanocytosis, have been reported to date. 1,6,8 Initial sequencing evaluation for single-nucleotide mutations in 25 genes (including NRAS and BRAF) revealed no mutations in biopsy samples from our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The activation of these signaling pathways leads to melanocyte growth, proliferation, survival, and transformation. 1 Although inhibition of the MAPK pathway has been targeted in the treatment of numerous malignancies (including melanoma), no reports of its successful use in the treatment of benign cellular proliferations, such as complex GCMNs and neurocutaneous melanocytosis, have been reported to date. 1,6,8 Initial sequencing evaluation for single-nucleotide mutations in 25 genes (including NRAS and BRAF) revealed no mutations in biopsy samples from our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is an estimated incidence of ∼1 in 20 000 to 500 000 live births. 1,2 GCMNs are caused by somatic mosaicism in melanocytic precursors. NRAS mutations can be found in 80% to 95% of GCMNs and result in the activation of the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways, which ultimately increases the proliferation and survival of melanocytes.…”
mentioning
confidence: 99%
“…Literature reports 14 somatic mutations in one study noted in 21 patients with CMN, with 57% of the lesions showing mutations in the NRAS gene [8]. Another study found a gain of function mutation in the NRAS gene associated with GCMN, ultimately leading to an abnormal proliferation of melanoblasts [9]. Some literature reports BRAFactivating mutations (single-nucleotide variants and fusions) activate the MAPK pathway [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances include the use of carbon dioxide and ruby laser, Er: YAG and Q-switched, respectively, for selective treatment of deep pigmentations and resurfacing [2]. With studies showing a link to mutations in the NRAS gene, the role of inhibitors of NRAS and high hydrostatic pressure inactivating the nevus tissue is also being considered [9].…”
Section: Discussionmentioning
confidence: 99%
“…There is a risk of malignant transformation both in prepubertal and post pubertal patients which is higher in larger lesions. The risk of transformation of GCMN(giant congenital melanocytic nevi) to melanoma is estimated between 0 to 3.8% (4,5). Another complication associated with GCMN is neurocutaneous melanosis (NCM), characterized by abnormal melanosis of the central nervous system (6).…”
Section: Introductionmentioning
confidence: 99%